Multigene CRISPR/Cas9 genome editing of hybrid proline rich proteins (HyPRPs) for sustainable multi-stress tolerance in crops: the review of a promising approach - Saikia, Banashree; Singh, Sanjay; Debbarma, Johni; Velmurugan, Natarajan; Dekaboruah, Hariprasanna; Arunkumar, Kallare P.; Chikkaputtaiah, Channakeshavaiah (Physiology and molecular biology of plants, 2020)
The recent global climate change has directly impacted major biotic and abiotic stress factors affecting crop productivity worldwide. Therefore, the need of the hour is to develop sustainable multiple stress tolerant crops through modern biotechnological approaches to cope with climate change. Hybrid proline rich proteins (HyPRPs) are the cell-wall structural proteins, which contain an N-terminal repetitive proline-rich domain and a C-terminal conserved eight-cysteine motif domain. HyPRPs are known to regulate multiple abiotic and biotic stress responses in plants. Recently, a few HyPRPs have been characterized as negative regulators of abiotic and biotic stress responses in different plants. Disruption of such negative regulators for desirable positive phenotypic traits has been made possible through the advent of advanced genome engineering tools. In the past few years, CRISPR/Cas9 has emerged as a novel breakthrough technology for crop improvement by target specific editing of known negative regulatory host genes. Here, we have described the mechanism of action and the role of known HyPRPs in regulating different biotic and abiotic stress responses in major crop plants. We have also discussed the importance of the CRISPR/Cas9 based genome editing system in targeting known negative regulatory HyPRPs for multi-stress crop tolerance using the tomato crop model. Application of genome editing to manipulate the HyPRPs of major crop plants holds promise in developing newer stress management methods in this rapidly changing climate and would lead in the future to sustain crop productivity.